Step * 1 4 1 1 1 1 of Lemma DAlembert-equation-iff


1. ∀f:ℝ ⟶ ℝ
     (((∃c:ℝ. ∀x:ℝ(f(x) rcos(c x))) ∨ (∃c:ℝ. ∀x:ℝ(f(x) cosh(c x))))
      (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))))
        ∧ (f(r0) r1)))
2. ∀f:ℝ ⟶ ℝ
     (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))) ∧ (f(r0) r1))
      ((∀x:ℝ(f(-(x)) f(x)))
        ∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
        ∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))))
3. : ℝ ⟶ ℝ
4. ∀x,y:ℝ.  ((x y)  (f(x) f(y)))
5. ∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))
6. f(r0) r1
7. (∀x:ℝ(f(-(x)) f(x)))
∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))
⊢ ¬¬((∃c:ℝ. ∀x:ℝ(f(x) rcos(c x))) ∨ (∃c:ℝ. ∀x:ℝ(f(x) cosh(c x))))
BY
Assert ⌜∃a:ℝ((r0 < a) ∧ (∀x:{x:ℝx ∈ [-(a), a]} (r0 < f(x))))⌝⋅ }

1
.....assertion..... 
1. ∀f:ℝ ⟶ ℝ
     (((∃c:ℝ. ∀x:ℝ(f(x) rcos(c x))) ∨ (∃c:ℝ. ∀x:ℝ(f(x) cosh(c x))))
      (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))))
        ∧ (f(r0) r1)))
2. ∀f:ℝ ⟶ ℝ
     (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))) ∧ (f(r0) r1))
      ((∀x:ℝ(f(-(x)) f(x)))
        ∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
        ∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))))
3. : ℝ ⟶ ℝ
4. ∀x,y:ℝ.  ((x y)  (f(x) f(y)))
5. ∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))
6. f(r0) r1
7. (∀x:ℝ(f(-(x)) f(x)))
∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))
⊢ ∃a:ℝ((r0 < a) ∧ (∀x:{x:ℝx ∈ [-(a), a]} (r0 < f(x))))

2
1. ∀f:ℝ ⟶ ℝ
     (((∃c:ℝ. ∀x:ℝ(f(x) rcos(c x))) ∨ (∃c:ℝ. ∀x:ℝ(f(x) cosh(c x))))
      (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))))
        ∧ (f(r0) r1)))
2. ∀f:ℝ ⟶ ℝ
     (((∀x,y:ℝ.  ((x y)  (f(x) f(y)))) ∧ (∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))) ∧ (f(r0) r1))
      ((∀x:ℝ(f(-(x)) f(x)))
        ∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
        ∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))))
3. : ℝ ⟶ ℝ
4. ∀x,y:ℝ.  ((x y)  (f(x) f(y)))
5. ∀x,y:ℝ.  ((f(x y) f(x y)) (r(2) f(x) f(y)))
6. f(r0) r1
7. (∀x:ℝ(f(-(x)) f(x)))
∧ (∀n:ℤ. ∀y:ℝ.  (f(r(n 1) y) ((r(2) f(y) f(r(n) y)) f(r(n 1) y))))
∧ (∀t:ℝ((f((t/r(2))) f((t/r(2)))) (f(t) r1/r(2))))
8. ∃a:ℝ((r0 < a) ∧ (∀x:{x:ℝx ∈ [-(a), a]} (r0 < f(x))))
⊢ ¬¬((∃c:ℝ. ∀x:ℝ(f(x) rcos(c x))) ∨ (∃c:ℝ. ∀x:ℝ(f(x) cosh(c x))))


Latex:


Latex:

1.  \mforall{}f:\mBbbR{}  {}\mrightarrow{}  \mBbbR{}
          (((\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  (f(x)  =  rcos(c  *  x)))  \mvee{}  (\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  (f(x)  =  cosh(c  *  x))))
          {}\mRightarrow{}  (((\mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y))))
                \mwedge{}  (\mforall{}x,y:\mBbbR{}.    ((f(x  +  y)  +  f(x  -  y))  =  (r(2)  *  f(x)  *  f(y)))))
                \mwedge{}  (f(r0)  =  r1)))
2.  \mforall{}f:\mBbbR{}  {}\mrightarrow{}  \mBbbR{}
          (((\mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y))))
          \mwedge{}  (\mforall{}x,y:\mBbbR{}.    ((f(x  +  y)  +  f(x  -  y))  =  (r(2)  *  f(x)  *  f(y))))
          \mwedge{}  (f(r0)  =  r1))
          {}\mRightarrow{}  ((\mforall{}x:\mBbbR{}.  (f(-(x))  =  f(x)))
                \mwedge{}  (\mforall{}n:\mBbbZ{}.  \mforall{}y:\mBbbR{}.    (f(r(n  +  1)  *  y)  =  ((r(2)  *  f(y)  *  f(r(n)  *  y))  -  f(r(n  -  1)  *  y))))
                \mwedge{}  (\mforall{}t:\mBbbR{}.  ((f((t/r(2)))  *  f((t/r(2))))  =  (f(t)  +  r1/r(2))))))
3.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
4.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y)))
5.  \mforall{}x,y:\mBbbR{}.    ((f(x  +  y)  +  f(x  -  y))  =  (r(2)  *  f(x)  *  f(y)))
6.  f(r0)  =  r1
7.  (\mforall{}x:\mBbbR{}.  (f(-(x))  =  f(x)))
\mwedge{}  (\mforall{}n:\mBbbZ{}.  \mforall{}y:\mBbbR{}.    (f(r(n  +  1)  *  y)  =  ((r(2)  *  f(y)  *  f(r(n)  *  y))  -  f(r(n  -  1)  *  y))))
\mwedge{}  (\mforall{}t:\mBbbR{}.  ((f((t/r(2)))  *  f((t/r(2))))  =  (f(t)  +  r1/r(2))))
\mvdash{}  \mneg{}\mneg{}((\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  (f(x)  =  rcos(c  *  x)))  \mvee{}  (\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  (f(x)  =  cosh(c  *  x))))


By


Latex:
Assert  \mkleeneopen{}\mexists{}a:\mBbbR{}.  ((r0  <  a)  \mwedge{}  (\mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  [-(a),  a]\}  .  (r0  <  f(x))))\mkleeneclose{}\mcdot{}




Home Index